Bandstru cture observation of graphene nanoribb on and boron-nitride nanoribbon embedded graphene nanoribbon - Haque, Fatin Farhan; Duity, Rimi Reza; Authoi, Syed Shamsia Tanzin (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.